Fiscal Federalism Model in Nepal: An Analytical Study - Shah, R. K. (Tribhuvan University Journal, 2016)
The Constitution of Nepal as Federal Democratic Republic was promulgated on September 20, 2015 by the second CA. The primary objective of this study is to review the modality presented in the new constitution on the natural resources, economic rights and revenue allocation. The study finds that the fiscal decentralization initiatives have not been successful in minimizing the political, social, economic, regional and ethnic inequalities inherent for nearly 240 years of a unitary system of governance in Nepal. The study recommends that VAT and income taxes will have to be collected concurrently at both the central and sub-national levels. Other taxes including excise duties will have to be collected by the sub-national governments which will support the expenditure responsibilities of the sub national governments adequately in federal Nepal. Intergovernmental transfer modality has to be included in the constitution. National Natural Resources and Fiscal Commission (NNRFC) have been constituted at the central level to make national level development plans and to make recommendations for additional grants and loans. A State Planning Commission (SPC) and a State Fiscal Commission (SFC) can be established in each state to prepare state development plans and to deal with the transfers to be made to local bodies.